Affinity chromatography of glycosidases - Ledvina, M; Kraml, J; Kolínská, J (Acta Universitatis Carolinae. Medica. Monographia, 1977)
The authors studied the separation of glucoamylase and beta-galactosidases from the interstinal mucosa of young rats by affinity chromatography. They tested the following chromatographic materials: p-aminophenyl-beta-D-thioglucoside bound to Sepharose 4B via hexamethylenediamine, gluconate and galactonate bound in different ways to Sepharose 4B and phlorizin bound by an azo-coupling reaction to a spacer attached to Sepharose 4B. The conditions of the adsorption of glycosidases to these materials and their subsequent elution were studied. Using chromatography on Sepharose 4B with a beta-thioglucoside affinant, we succeeded in purifying lactase preparation so that, in electrophoresis on polyacrylamide gel, it formed a single zone identical with 1-naphthyl-beta-glucosidase activity.
Keywords: Glucosides; chromatografie afinitní; glykosidhydrolasy; Chromatography, Affinity; Glycoside Hydrolases; glukosidy